Rapid Identification of Emerging Pathogens: Coronavirus - Rangarajan Sampath; Steven A. Hofstadler; Lawrence B. Blyn; Mark W. Eshoo; Thomas A. Hall; Christian Massire; Harold M. Levene; James C. Hannis; Patina M. Harrell; Benjamin Neuman; Michael J. Buchmeier; Yun Jiang; et al. (Emerging Infectious Diseases, 2005)
We describe a new approach for infectious disease surveillance that facilitates rapid identification of known and emerging pathogens. The process uses broad-range polymerase chain reaction (PCR) to amplify nucleic acid targets from large groupings of organisms, electrospray ionization mass spectrometry for accurate mass measurements of PCR products, and base composition signature analysis to identify organisms in a sample. We demonstrate this principle by using 14 isolates of 9 diverse Coronavirus spp., including the severe acute respiratory syndrome–associated coronavirus (SARS-CoV). We show that this method could identify and distinguish between SARS and other known CoV, including the human CoV 229E and OC43, individually and in a mixture of all 3 human viruses. The sensitivity of detection, measured by using titered SARS-CoV spiked into human serum, was ≈1 PFU/mL. This approach, applicable to the surveillance of bacterial, viral, fungal, or protozoal pathogens, is capable of automated analysis of >900 PCR reactions per day.